Quantification of maximal force produced in standard and contra-standard sculling in synchronized swimming. A pilot study - Diogo, V.; Soares, S.; Tourino, C.; Carmo, C.; Aleixo, I.; Morouco, P.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (The Open Sports Sciences Journal, 2010)
Studies carried out in synchronized swimming are very scarce, namely those which include biomechanical analysis of the sculling technique. The purpose of this study was to measure the maximal force produced in standard and contra-standard sculling, using a 30s maximal tethered synchronized swimming test. One former female synchronized swimmer and one former female swimmer performed a 2x30s maximum intensity tethered synchronized swimming test, in standard and contra-standard sculling conditions, respectively. Parameters studied were maximal, mean and minimum force, the time when maximal and minimum force occurred, and fatigue index. Results showed that the higher values of maximal and mean force were found in standard sculling, both for the synchronized swimmer and the swimmer. The swimmer attained higher values of absolute and relative maximal force in the standard sculling, but lower values in the contra-standard technique, when compared to the synchronized swimmer. Fatigue Index results evidence that the maximal force declined during the 30s in both participants and in both sculling conditions. This parameter was higher for the contra-standard sculling performed by the swimmer, and for the standard sculling for the synchronized swimmer. In conclusion, there were differences in force production in standard and contra-standard sculling between a swimmer and a synchronized swimming. Those differences could probably be explained by differences in skill competence.